Statins and Lung Cancer: A Review of Current Literature - W. Kurtis, Childers; Nathaniel, Melton; Daniel, Goldman; Troy, Moritz (Journal of Neoplasms, 2018)
Cardiovascular disease and lung cancer are two of the most common causes of death in the United States. The cardioprotective benefits of statin class drugs is predominantly mediated through the inhibition of 3-hydroxy-3-methylglutaryl CoA (HMG-CoA) reductase, decreasing available mevalonate, and thus limiting in vivo cholesterol biosynthesis. Mevalonate and its metabolites have significant roles in cellular membrane synthesis, which is dysregulated during tumorigenesis, and is therefore a potential source for anti-tumor effects of statins. Similarly, dysregulation of cellular signaling is a hallmark of tumorigenesis. In vitro studies of EGFR, RAS, and AKT signaling pathways in cancer cells can all be reformed back to states more indicative of normally functioning cells when treated with statins. Statins have also been shown to exert beneficial properties in the presence of chemotherapeutic medications and radiation therapies by modulating the deleterious effects of reactive oxygen species, decreasing tumor cell resistance, and minimizing damage to surrounding native tissues. There is abundant of in vitro evidence to support the beneficial effects of statins on lung cancer patients. Prospective studies to determine the value of statin therapy on lung cancer prevention could lead to a significant change in lung cancer treatment.
Keywords: Lung cancer; Epidermal growth factor receptor (EGFR); malignant cells; tyrosine kinase inhibitors (TKI)